The missing golden ticket and other splendiferous secrets - Dahl, Roald; Blake, Quentin (Puffin Books New York, 2013)
Containing excerpts from earlier tributes to Dahl's work and wit, this is an eclectic and funny collection of tidbits by and about the late author. It also features a missing chapter from "Charlie and the Chocolate Factory."